α4β7 integrin-dependent adhesion of T cells to MAdCAM-1 is blocked by vedolizumab in patients with chronic refractory pouchitis - Melde, Michaela; Müller, Tanja; Schneider, Ignaz Hans Friedrich; Geppert, Carol-Immanuel; Mühl, Laura; Besendorf, Laura; Allner, Clarissa; Becker, Emily; Atreya, Imke; Vitali, Francesco; Atreya, Raja; Neurath, Markus; et al. (Therapeutic Advances in Gastroenterology, 2021)
Background: The anti-α4β7 integrin antibody vedolizumab is an established therapeutic option for the treatment of inflammatory bowel disease (IBD). It has also been successfully used in patients with chronic antibiotic-refractory pouchitis following proctocolectomey with ileal pouch-anal anastomosis. However, the expression and function of gut-homing markers as well as strategies to predict the response to vedolizumab in pouchitis are understudied so far. Methods: We used flow cytometry and dynamic adhesion assays to study the expression and function of gut-homing integrins on T cells from patients with pouchitis and controls as well as longitudinally during therapy of pouchitis with vedolizumab. Moreover, we describe clinical effects of vedolizumab in a cohort of patients with pouchitis. Results: T cells from patients with pouchitis express a specific profile of gut-homing integrins. Integrin α4β7 on T cells from patients with pouchitis mediates adhesion to mucosal addressin cell adhesion molecule (MAdCAM)-1, which can be blocked by vedolizumab in vitro. Vedolizumab efficiently treats pouchitis in a portion of patients and response correlates with dynamic adhesion profiles to MAdCAM-1. Conclusion: Our data suggest that T cell trafficking seems to be important for the pathogenesis of pouchitis and support the therapeutic use of vedolizumab. Integrin function might serve as a biomarker to predict response to vedolizumab.
CRIS-Team Scopus Importer:2021-12-17
Keywords: ileal pouch-anal anastomosis; pouchitis; proctocolectomy; T cells trafficking; vedolizumab